Effect of four weeks' high dose ipratropium bromide treatment on lung mucociliary clearance. Issue 4 (April 1986) - Taylor, R G; Pavia, D; Agnew, J E; Lopez-Vidriero, M T; Newman, S P; Lennard-Jones, T; Clarke, S W
Abstract : In a randomised, double blind crossover study the effect of high dose ipratropium bromide (200 micrograms three times daily given by metered dose inhaler for four weeks) on lung mucociliary clearance and on the wet weight and mean apparent viscosity of sputum was compared with that of placebo. Six smokers, six ex-smokers, and three non-smokers (12 men and three women, median age 60 years) were studied. Eight subjects had chronic obstructive lung disease (median FEV1 46% predicted) and seven had asthma (FEV1 70% predicted). Seven subjects produced sputum regularly, two of whom had asthma. Clearance of secretions was measured by an inhaled radioaerosol technique. The number of coughs and the wet weight, radioactive content, and mean apparent viscosity of sputum produced during the six hour observation period were recorded, as was the mean wet weight of sputum produced during the last two 24 hour periods ending each treatment. Comparison with placebo showed that treatment with high dose ipratropium bromide was associated with a significant increase in the penetration index of inhaled particles, but there was no significant change in alveolar deposition of particles or in tracheobronchial clearance, uncorrected or corrected for sputum expectorated. The wet weight of sputum produced, its radioactive content, and mean apparent viscosity were similar after treatment with ipratropium bromide and placebo. These results show that high dose inhaled treatment with the synthetic anticholinergic bronchodilator ipratropium bromide for four weeks is not associated with detectable modification of the clearance of secretions from the lungs, or of sputum volume or viscosity.